Pengaruh Gaya Kepemimpinan Kepala Sekolah Guru Penggerak terhadap Kinerja Guru - Apriliani, Ika Fariatul; Taufiqulloh, Taufiqulloh; Prihatin, Yoga (Universitas Nusantara PGRI Kediri, 2026)
Leadership plays a crucial role in shaping teacher performance, particularly in the context of educational transformation in Indonesian schools led by principals who graduated from the Teacher Leadership program. This study aims to analyze the influence of various leadership styles directive, supportive, participatory, and goal-focused on junior high school teacher performance. A quantitative approach was used, collecting data through questionnaires distributed to 75 teachers from three public junior high schools in Bantarbolang District. The data were analyzed using multiple linear regression to determine the influence of each leadership style. The results indicate that all four leadership styles significantly influence teacher performance, with supportive leadership being the most dominant. These findings emphasize the importance of adaptive and empowering leadership practices aligned with teacher needs. This study contributes to the development of educational leadership in Indonesia by providing empirical evidence as a basis for improving principal training and performance-based leadership strategies.